Political Culture Patterns of the Mandar Community in Palu - Rezki Rahmawati; Muhammad Iqbal Maulana (Kirana Publisher (KNPub), 2023)
Migrant communities in an area have distinctive patterns both in social life, electoral politics, and non-electoral. Typical patterns will be repeated and become political culture. In this study, the author looks at the political culture of the Mandar people in Palu City, considering that the Mandar people have lived in the town of Palu for a long time. This research is a descriptive qualitative research conducted to find out the political culture patterns of immigrant communities. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the type of political culture of the Mandar people in Palu is the type of political culture of the participants. This is shown by the cognitive, affective, and evaluative aspects of the Mandar community which are suitable for all political aspects such as the general system, input objects, and political output objects. Participant political culture in the Mandar community in Palu City results from the level of education and open access to information in the urban environment.